Transnasal-brain delivery of nanomedicines for neurodegenerative diseases - Zhang, Xu; Wang, Maohua; Liu, Zhixian; Wang, Ying; Chen, Li; Guo, Jiaqi; Zhang, Wentao; Zhang, Yao; Yu, Chenjie; Bie, Tongwu; Yu, Youjun; Guan, Bing (Frontiers in Drug Delivery, 2023)
Neurodegenerative diseases (NDs) have become a serious global health problem as the population ages. Traditionally, treatment strategies for NDs have included oral and intravenous administration; however, the blood-brain barrier (BBB) can prevent drugs from reaching the brain, rendering the treatment incomplete and the effect unsatisfactory. Additionally, the prolonged or excessive use of drugs that can cross the BBB can damage liver and kidney function. Recent studies have shown that nose-to-brain drug delivery can noninvasively bypass the BBB, allowing drugs to enter the brain through the olfactory or trigeminal nerve pathways; additionally, nanoparticle carriers can enhance drug delivery. This review introduces drug carrier nanoparticles for nose-to-brain delivery systems, compares the advantages and disadvantages of different nanoparticles, and discusses the factors influencing nose-to-brain nanomedicine delivery and enhancement strategies. We also summarize nose-to-brain delivery and nanomedicines for treating NDs, the current challenges of this approach, and the future promise of nanomedicine-based ND treatment.